2021
DOI: 10.3390/toxins13060425
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Temperature and Toxic Algal Abundance on Paralytic Shellfish Toxic Accumulation, Tissue Distribution and Elimination Dynamics in Mussels Mytilus coruscus

Abstract: This study assessed the impact of increasing seawater surface temperature (SST) and toxic algal abundance (TAA) on the accumulation, tissue distribution and elimination dynamics of paralytic shellfish toxins (PSTs) in mussels. Mytilus coruscus were fed with the PSTs-producing dinoflagellate A. catenella under four simulated environment conditions. The maximum PSTs concentration was determined to be 3548 µg STX eq.kg−1, which was four times higher than the EU regulatory limit. The increasing SST caused a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The natural seawater was previously filtered through a sand filter and treated with UV light, and a total water exchange was performed daily in all trials. Animals were fed daily with a mixture of live (Dunaliella tertiolecta and Chaetoceros calcitrans) and frozen (Tetraselmis chuii) microalgae, at a concentration of ~100,000 cells/day/animal [34].…”
Section: Animal Collection and Maintenancementioning
confidence: 99%
“…The natural seawater was previously filtered through a sand filter and treated with UV light, and a total water exchange was performed daily in all trials. Animals were fed daily with a mixture of live (Dunaliella tertiolecta and Chaetoceros calcitrans) and frozen (Tetraselmis chuii) microalgae, at a concentration of ~100,000 cells/day/animal [34].…”
Section: Animal Collection and Maintenancementioning
confidence: 99%
“…A limited number of studies have shown that the ability to accumulate PSTs between M. galloprovincialis and A. irradians was significantly different. Some studies have shown that after exposure to A. catenella at a density of 5.6 × 10 6 cells/mL, the concentration of PSTs in Mytilus coruscus was 1864 µg/kg (the regular standard is 800 µg/kg) [38]. After exposure to A. tamarense at a density of 1.26 × 10 4 cells/mL, the concentration in A. irradians was 49.4 MU/g (the regular standard is 4 MU/g) [39].…”
Section: Differences In Physiological Characteristics Between M Gallo...mentioning
confidence: 99%
“…The cellular toxin content of P. bahamense might increase with a lower growth rate and remains unaffected by different growth conditions (Usup et al, 2012). Microalgae release toxins in the water body and toxicity levels of shellfish are affected by the abundance and duration of exposure to the toxic microalgae (Tang et al, 2021). In this study, a post-column oxidation HPLC-FLD method was performed according to Oshima (1995) to analyse the toxin level and profile of P. bahamense at different culture ages (60, 120, 180, and 360 days) after the death phase to see how long the toxin can be sustained and bloom according to the AOAC Official Method 2011.02 (AOAC International, 2011).…”
Section: Introductionmentioning
confidence: 99%